Effects of carbon sources on production performance, enzymatic efficiency and biochemical indices of Nile tilapia under biofloc culture system - Aslam, Nudrat; Mateen, Abdul; Zahra, Kainat; Abbas, Amna; Dureshahwar, .; Rubab, Sania; Razaq, Salyha (Journal of Fisheries, 2025)
Biofloc technology (BFT) is a sustainable aquaculture system based on the principle of nutrient recycling. This study evaluated the effects of starch, molasses and corn flour as carbon sources on water quality, growth performance, proximate body composition, hematological indices, immune responses and antioxidant status of Nile tilapia in biofloc system. A 12-week trial was conducted with juvenile Nile tilapia (25.3 ± 0.6 g), which were randomly assigned to four treatments. The treatments were BFT with corn flour (BFT+CF), molasses (BFT+M), starch (BFT+S) and a control group. Physicochemical parameters of water were affected by the carbon sources but remained within the optimal range for tilapia culture, with the highest biofloc volume (34.1 mL L–1) observed in BFT+M. Growth performance was significantly increased in BFT+M, which yielded the superior weight gain (125 g), survival rate (99.03%) and the lowest feed conversion ratio (17.1). Proximate analysis revealed the highest crude protein levels in fish reared under BFT+M and BFT+S. Hematological parameters (hematocrit, hemoglobin, WBCs and RBCs) and non-specific immune responses (albumin, globulin, immunoglobulin and lysozyme activity) were significantly improved in BFT+M and BFT+S groups compared to the control. In conclusion, the supplementation of biofloc system with molasses and starch as carbon sources significantly improved growth performance, hematology, immunity and antioxidant capacity of Nile tilapia.